Weak Grip Strength and its association with disability and impaired physical performance in elderly over 80 years - Runzer-Colmenares, Fernando M. (2023)
Introduction. Weak grip strength is a well-known associated factor with disability and physical performance, but this association is controversial in older adults aged 80 years or more. Objective. To determine the association between prehensile strength and functional dependence and physical performance among adults older than 80 years. Methods. This research was an analytical, cross-sectional study, conducted in 147 older adults aged 80 years or more, from Naval Peruvian Service. We included assessments about muscle strength, physical performance, disability, anthropometric variables, and nutritional assessment. Results. We found a significant association between weak grip strength and dependence for basic activities of daily living (aOR: 2.81, 95% CI: 1.32 to 10.11), as well as altered physical performance (aOR: 4.32, 95% CI: 1.97 to 9.59), these associations were independent of age, number of comorbidities, geriatric syndromes, hemoglobin, ferritin, glucose, total cholesterol, lymphocytes, vitamin B12, triglycerides, serum albumin, MMSE score, calf circumference, brachial circumference, BMI, level of education, marital status, sex, and waist/hip ratio. Conclusions. In persons older than 80 years, having weak grip strength was associated with weak muscle strength and poor physical performance. Our results could be useful for the inclusion of these measures within care protocols for elderly and high comorbidity populations. With this, it seeks to improve the integrity and care of geriatric patients.